Critical factors in the successful expansion of Pneumococcal Conjugate Vaccine in India during the COVID-19 pandemic - Seema Singh Koshal; Arindam Ray; Rhythm Hora; Amanjot Kaur; Syed F Quadri; Rashmi Mehra; Amrita Kumari; Pradeep Haldar; Arup Deb Roy (Vaccine: X, 2023)
India had decided to roll out PCV in India in 2015, but successful implementation of any new vaccine introduction mandates an enormous effort. PCV was scaled up during the COVID-19 pandemic, which posed new, unprecedented challenges in the vaccine rollout. However, India successfully expanded PCV in the country in record time across all states and Union Territories.During the pandemic, supply-side restrictions, delayed vaccine shipments, staff shortages, and restrictions in conducting training negatively affected the roll-out of PCV across the country. However, despite the ongoing pandemic, India successfully rolled out PCV across the country in 7 months. In this review, the authors have conducted a narrative review to delineate the crucial factors that helped in the successful expansion of PCV.